1982
DOI: 10.1056/nejm198212093072401
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacytidine Selectively Increases γ-Globin Synthesis in a Patient with β+Thalassemia

Abstract: 5-Azacytidine is a cytidine analogue that is capable of activating repressed genes in tissue-culture cells and has been shown to increase hemoglobin-F production in anemic baboons. This drug was administered to a patient with severe beta-thalassemia in an attempt to stimulate hemoglobin-F production. After seven days of 5-azacytidine treatment, gamma-globin synthesis increased approximately sevenfold, temporarily normalizing the patient's unbalanced globin synthesis. Erythropoiesis became more effective, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
216
0
12

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(231 citation statements)
references
References 32 publications
3
216
0
12
Order By: Relevance
“…Its ability to stimulate HbF production was also demonstrated in a small number of patients with SCD and β-thalassemia. 5,6 Treatment with 5-azacytidine resulted in a significant increase in the level of HbF that was associated with a decrease in the fraction of dense cells in patients with SCD. Treatment with this drug also led to a partial correction of the non-α:α chain imbalance and a decrease in transfusion requirements in few patients with β-thalassemia.…”
Section: -Azacytidinementioning
confidence: 99%
“…Its ability to stimulate HbF production was also demonstrated in a small number of patients with SCD and β-thalassemia. 5,6 Treatment with 5-azacytidine resulted in a significant increase in the level of HbF that was associated with a decrease in the fraction of dense cells in patients with SCD. Treatment with this drug also led to a partial correction of the non-α:α chain imbalance and a decrease in transfusion requirements in few patients with β-thalassemia.…”
Section: -Azacytidinementioning
confidence: 99%
“…These observations stimulated the development of clinical trials of 5-azacytidine in a small number of sickle cell anemia and β-thalassemia patients. These trials showed that 5-azacytine treatment elicited in these patients an increase of HbF synthesis and reduced the level of anemia [88,97,98].…”
Section: Chemical Inducers Of Hbf Synthesismentioning
confidence: 97%
“…5-Azacytidine (5-Aza) was the first agent able to reactivate HbF synthesis in humans used for the treatment of β-thalassemia [88] and sickle cell disease [89] patients. The mechanism through which 5-Aza stimulates HbF synthesis is unclear.…”
Section: Chemical Inducers Of Hbf Synthesismentioning
confidence: 99%
“…Appreciation of the role of DNA methylation in gene silencing led to the use of 5-azacytidine, an inhibitor of methyltransferase, to induce fetal hemoglobin (HbF) production in baboons and later in patients with SCD and b-thalassemia [1][2][3]. Although 5-azacytidine was shown to be an effective inducer of HbF in patients with b-thalassemia and SCD, large-scale clinical trials with this agent were never performed because of concerns over its potential toxicities.…”
mentioning
confidence: 99%